Dr. Muhammad Sharif's Critique of Dr. Al-Dhahabi on the Issue of Renewal: A Critical Analytical Study - Muhammad Abdul Aziz (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2025)
This study critically examines Dr. Muhammad Sharif’s perspective on the concept of tajdīd (renewal) as articulated by Dr. Muhammad al-Dhahabi, with particular attention to his objection to al-Dhahabi’s claim that the early scholars left no room for contribution by later generations. The study also assesses the extent to which Dr. Sharif maintained scholarly objectivity and fairness in his critique, avoiding blind partisanship and methodological shortcomings that could weaken academic criticism. The research adopts a critical-evaluative approach by comparing the viewpoints of both scholars and analyzing them through an objective academic lens. The findings indicate that, in general, Dr. Sharif demonstrated a commendable adherence to the principle of fairness in his critical approach. Nonetheless, the study identified certain instances where he appeared to withhold justifiable defense from Dr. al-Dhahabi, such as in the latter’s omission of several contemporary exegetes in his scholarly treatment.